2016
DOI: 10.1007/s11856-016-1303-z
|View full text |Cite
|
Sign up to set email alerts
|

Measure partitions using hyperplanes with fixed directions

Abstract: We study nested partitions of R d obtained by successive cuts using hyperplanes with fixed directions. We establish the number of measures that can be split evenly simultaneously by taking a partition of this kind and then distributing the parts among k sets. This generalises classical necklace splitting results and their more recent high-dimensional versions. With similar methods we show that in the plane, for any t measures there is a path formed only by horizontal and vertical segments using at most t−1 tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…A similar problem has been considered if only vertical and horizontal segments are allowed. It is conjectured that n+1 measures can be split evenly using a path that only has n turns , as opposed to the 3n2 measures we can split with the result above. If the condition on the directions of the paths is completely dropped, we get an interesting problem: Problem Given a polygonal path in the plane that uses at most n turns, what is the largest number of measures that we can always guarantee to be able to split simultaneously by half?…”
Section: Open Questions and Remarksmentioning
confidence: 79%
See 1 more Smart Citation
“…A similar problem has been considered if only vertical and horizontal segments are allowed. It is conjectured that n+1 measures can be split evenly using a path that only has n turns , as opposed to the 3n2 measures we can split with the result above. If the condition on the directions of the paths is completely dropped, we get an interesting problem: Problem Given a polygonal path in the plane that uses at most n turns, what is the largest number of measures that we can always guarantee to be able to split simultaneously by half?…”
Section: Open Questions and Remarksmentioning
confidence: 79%
“…A partition of Rd into convex parts is an iterated hyperplane partition if it can be made out of Rd by successively partitioning each convex part, from a previous partition, with a hyperplane (that means each new hyperplane only cuts one of the existing convex parts, see Figure ). In the authors showed that for r thieves and m measures in Rd, there is a fair distribution of each measure among the thieves using an iterated hyperplane partition that has (r1)m hyperplane cuts, whose directions are fixed in advance, as long as r is a prime power. This has the advantage that the total number of parts is (r1)m+1.…”
Section: Introductionmentioning
confidence: 99%
“…Deligkas et al [22] studied the computational complexity of the exact version of the problem, and obtained among other results its membership in a newly introduced class BU (for "Borsuk-Ulam" [12]) and its computational hardness for the well-known class FIXP of Etessami and Yannakakis [25]. Very recently, Deligkas et al [21] showed the PPA-completeness of the related Pizza Sharing problem [35], via a reduction from Consensus-Halving.…”
Section: Related Workmentioning
confidence: 99%
“…Kano conjectured that for any n smooth measures in R 2 there exists a path formed only by horizontal and vertical segments, that takes at most n − 1 turns, that simultaneously halves each measure. The conjecture is only known for k = 1, 2 or if the path is allowed to go through infinity [UKK09,KRPS16]. We wonder if the following way to mix Kano's conjecture with Theorem 2.1 holds.…”
Section: Remarks and Open Problemsmentioning
confidence: 99%